The agrifood system in South Asia: Pathways to sustainable healthy diets - International Food Policy Research Institute; Scott, Samuel P.; Kishore, Avinash; Headey, Derek D. (International Food Policy Research Institute, 2025)
South Asia is home to an estimated 2.08 billion people, making it the most densely populated region on the planet. This places immense pressure on the region’s agrifood systems to ensure that healthy and affordable food is available for all, a goal that can only be met by addressing today’s multiple interconnected challenges. Overcoming bottlenecks in agrifood systems — the networks of actors, activities, infrastructure, and policies that are involved in getting food from farms to mouths — requires data and evidence on the many elements of these complex systems. Moreover, that evidence must serve as a catalytic driver of change, which further requires strong partnerships between donors, researchers, civil society, industry, and policymakers.